Oil and gas well rate estimation by choke formula: semi-analytical approach - Mohammad Ali Kargarpour (Journal of Petroleum Exploration and Production Technology, 2019)
Abstract During last decades accurate two-phase flow meters are introduced to upstream oil and gas industry; however, due to economic and technical issues, the use of choke formula for estimating well production rate is still popular. After its first introduction by Gilbert (Flowing and gas-lift well performance. API Drilling Production Practice 20:126–157, 1945), several other formulas were developed, either with global purposes or targeting a specific reservoir. All of these Gilbert-type choke formulas assume sonic flow conditions through a well head choke; for this reason, they do not consider the differential pressure across the choke. The other types of choke formulas which are introduced by some pioneer researchers (Fortunati, Two-Phase Flow Through Wellhead Chokes. Paper SPE 3742, 1972; Ashford, Pierce, The Determination of Multiphase Pressure Drops and Flow Capacities in Downhole Safety Valves, JPT, September, 1974) consider the subsonic velocity condition through the choke at expense of formula complication. Field experience reveals that there are cases in which the well flow rate is changed by changing the downstream separator operation pressure. In this paper, by using basic concepts of fluid mechanics, it is shown that the rate of two-phase flow through a choke generally depends on the pressure drop across the choke besides other factors by deriving a global choke formula. Based on this finding, a general Gilbert-type choke formula is derived which includes differential pressure across the choke. This new choke formula is validated using a field data bank including 399 data points.